THE ROLE OF DOCETAXEL AS FIRST-LINE CHEMOTHERAPY ON PSA LEVEL AND QOL IN CRPC PATIENTS - Seputra, Kurnia Penta; Nurhadi, Pradana; Satria, Hikmat (Indonesian Urological Association, 2024)
Objective: Prostate cancer is the second most common cancer in men and the fifth leading cause of death worldwide. 10-20% of cases can progress to a more aggressive stage called castration-resistant prostate cancer (CRPC) with a higher death rate. Clinical guidelines recommend docetaxel as first-line chemotherapy and evaluated using the PSA test. This study aims to investigate the effect of docetaxel chemotherapy on PSA levels in CRPC. Material & Methods: A retrospective study was conducted from January 2016 until August 2022 according to the medical records database Saiful Anwar Hospital. There were 16 patients who met the inclusion criteria, including male patients with a diagnosis of CRPC who received castration therapy and found an increase in PSA 3 times of nadir or found 2 or more bone metastatic lesions or soft tissue lesions > 2 cm, received 6 series of docetaxel chemotherapy, and have a PSA data was performed before and after chemotherapy. Statistical analysis was performed using a differential T-test. Results: The results, obtained were significantly different (p<0.05) on the average PSA (log) pre-post chemotherapy, visual analog scale (VAS), and quality of life, and not significantly different on BMI pre-post chemotherapy. Conclusion: 6 cycles of docetaxel chemotherapy resulted in a decrease in PSA levels of CRPC significantly. It showed an excellent response to docetaxel chemotherapy in managing CRPC patients. Limitations of this study were specifically the retrospective cohort study model and the ability to reduce PSA levels in assessing the prognosis of CRPC. Keywords: Castration-resistant prostate cancer, chemotherapy, docetaxel, prostate-specific antigen.